Daytime plasma drifts in the equatorial lower ionosphere. Issue 11 (4th November 2015) - Hui, Debrup; Fejer, Bela G.
Abstract: We have used extensive radar measurements from the Jicamarca Observatory during low solar flux periods to study the quiet time variability and altitudinal dependence of equatorial daytime vertical and zonal plasma drifts. The daytime vertical drifts are upward and have largest values during September–October. The day‐to‐day variability of these drifts does not change with height between 150 and 600 km, but the bimonthly variability is much larger in the F region than below about 200 km. These drifts vary linearly with height generally increasing in the morning and decreasing in the afternoon. The zonal drifts are westward during the day and have largest values during July–October. The 150 km region zonal drifts have much larger day‐to‐day, but much smaller bimonthly variability than the F region drifts. The daytime zonal drifts strongly increase with height up to about 300 km from March through October, and more weakly at higher altitudes. The December solstice zonal drifts have generally weaker altitudinal dependence, except perhaps below 200 km. Current theoretical and general circulation models do not reproduce the observed altitudinal variation of the daytime equatorial zonal drifts. Key Points: Equatorial plasma drifts have large altitude‐dependent variability The equatorial zonal plasma drifts increase strongly with height below 300 km Theoretical models do not account for the height dependence of the zonal drifts